1992
DOI: 10.1007/bf00056356
|View full text |Cite
|
Sign up to set email alerts
|

Secular ring instability in the protoplanetary accretion disk

Abstract: The aim of the present paper is to show that an accretion disk, the material of which satisfies the Navier-Stokes equations of a compressible fluid, is secularly unstable to axisymmetric density disturbances even if Toomre's parameter Q is greater than one. This instability process, which can also be interpreted as negative diffusion, leads immediately to the formation of rings in the accretion disk as an intermediate step in the formation of planets, at least for the outer gaseous ones. We believe that the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Notice also that the critical value of Q ≈ 2 predicted in our analysis is close to Salo (1992Salo ( , 1995, Willerding (1992), Osterbart and Willerding (1995), Sterzik et al (1995), andGriv et al (1999b) numerical results. 15 Summarizing, collective motion connected with the Jeans-unstable mode is excited in the plane of a disk of mutually gravitating particles when the random velocity dispersion is not sufficiently large, c r < (2Ω/κ)c T , in other words, if the effective Toomre's Q-value is Q < 2Ω/κ ∼ 2.…”
Section: The Jeans Oscillations -Weak and Rare Collisions (ωsupporting
confidence: 90%
See 1 more Smart Citation
“…Notice also that the critical value of Q ≈ 2 predicted in our analysis is close to Salo (1992Salo ( , 1995, Willerding (1992), Osterbart and Willerding (1995), Sterzik et al (1995), andGriv et al (1999b) numerical results. 15 Summarizing, collective motion connected with the Jeans-unstable mode is excited in the plane of a disk of mutually gravitating particles when the random velocity dispersion is not sufficiently large, c r < (2Ω/κ)c T , in other words, if the effective Toomre's Q-value is Q < 2Ω/κ ∼ 2.…”
Section: The Jeans Oscillations -Weak and Rare Collisions (ωsupporting
confidence: 90%
“…In fact, it should be made clear right from the start that the suggestion of hyperfine < ∼ 100 m structure in Saturn's rings due to the combined effects of gravity and interparticle collisions is not an entirely new idea. Salo (1992Salo ( , 1995, Willerding (1992), Richardson (1994), Osterbart and Willerding (1995), and Sterzik et al (1995) have already predicted such a structure in Saturn's rings by N -body computer simulations.…”
Section: Introductionmentioning
confidence: 89%
“…Viscosity-driven gravitational instability Viscous disks can also develop GI even when Q > 1. This is because, as demonstrated below, viscosity removes rotational support against self-gravity for longwavelength disturbances (Lynden- Bell & Pringle 1974;Willerding 1992;Gammie 1996). A similar effect occurs in dusty fluids where the required frictional forces are provided by dust-gas drag (Goodman & Pindor 2000;Ward 2000;Takahashi & Inutsuka 2014).…”
Section: Introductionmentioning
confidence: 86%
“…They claimed this instability to be analogous to the well‐known viscous mechanism that converts Maclaurin spheroids to Jacobi ellipsoids. Morozov, Torgashin & Fridman (1985), Willerding (1992), Griv et al (2000a) improved Lynden‐Bell and Pringle's calculation by taking into account the effect of non‐uniform rotation in a two‐dimensional self‐gravitating system 2 . It seems that N ‐body simulations have indicated that the densest parts of the B ring with optical depth τ > 1 can exhibit spontaneous viscous overstability (Salo, Schmidt & Spahn 2001).…”
Section: Introductionmentioning
confidence: 99%